2014
DOI: 10.1016/j.meegid.2014.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, distribution, and sequence diversity of hmwA among commensal and otitis media non-typeable Haemophilus influenzae

Abstract: Nontypeable Haemophilus influenzae (NTHi) are Gram-negative coccobacilli that colonize the human pharynx, their only known natural reservoir. Adherence to the host epithelium facilitates NTHi colonization and marks one of the first steps in NTHi pathogenesis. Epithelial cell attachment is mediated, in part, by a pair of high molecular weight (HMW) adhesins that are highly immunogenic, antigenically diverse, and display a wide range of amino acid diversity both within and between isolates. In this study, the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 46 publications
3
11
0
Order By: Relevance
“…HMW1A and HMW2A display wide amino acid diversity both within and between isolates, with the region of lowest sequence identity in the host cell binding domain, which has been predicted to affect tissue tropism and immune evasion [ 42 , 59 , 63 67 ]. Phylogenetic analyses of the HMW adhesin binding domain has revealed four distinct sequence clusters, and the majority of sequences belonging to one of two dominant sequence clusters [ 41 ]. Of note, 86-028NP and strain 12 hmw1A binding domains belong to clusters 4 and 2, respectively, which might contribute to their strong and intermediate phenotypes; future studies using mosaic proteins with binding domains from distinct clusters and using multiple human cell lines could identify any clade-specific functions for HMW proteins.…”
Section: Discussionmentioning
confidence: 99%
“…HMW1A and HMW2A display wide amino acid diversity both within and between isolates, with the region of lowest sequence identity in the host cell binding domain, which has been predicted to affect tissue tropism and immune evasion [ 42 , 59 , 63 67 ]. Phylogenetic analyses of the HMW adhesin binding domain has revealed four distinct sequence clusters, and the majority of sequences belonging to one of two dominant sequence clusters [ 41 ]. Of note, 86-028NP and strain 12 hmw1A binding domains belong to clusters 4 and 2, respectively, which might contribute to their strong and intermediate phenotypes; future studies using mosaic proteins with binding domains from distinct clusters and using multiple human cell lines could identify any clade-specific functions for HMW proteins.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to conclude on the clinical relevance of the limited (or no) effect of vaccination on overall NTHi carriage, especially if only a pathogenic subset of NTHi is actually responsible for clinical AOM. 70 By analogy, if one had only considered 7vCRM effects on overall pneumococcal colonization, with no net decrease, one might have concluded that the vaccine would not affect pneumococcal AOM; instead, it was necessary to look specifically at the vaccine-type carriage and vaccine-type pneumococcal disease.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are synthesized by ≈60% of NT Hi isolates, and 90% of these possess two HMW adhesin-coding genes25. Interestingly, hmw genes are present in strains 86–028NP26 and 37527, but absent in strain Rd KW20.…”
Section: Resultsmentioning
confidence: 99%